Unit root tests in the presence of structural breaks: Evidence from African stock markets - Osarumwense Osabuohien-Irabor (Economic Journal of Emerging Markets, 2020)
This paper examines whether stock prices for fourteen African countries are affected by transitory or permanent shocks. This study answers whether Africa stock market indices are mean-reverting or random-walk in the presence of multiple structural breaks. To investigate African equity price behavior, we considered one and two endogenously determined structural break tests of Zivot and Andrews (1992) and Lumsdaine and Papell (1997), respectively. Findings/Originality: Our results show that almost all African equity price indices follow the random walk processes except for Senegal and Botswana, which exhibit mean-reversion properties in its equity prices. It implies that investors in African stock markets cannot rely on past information and behavior to predict stock market movements or develop their trading strategies. The result also confirms that the Augmented Dickey-Fuller (ADF) unit root test is not applicable in the presence of structural breaks in African stock markets.